The Impact of Organizational Climate on Organizational Citizenship Behavior (OCB) in a Multicultural Work Environment - Ario Wibowo, Ugung Dwi; Taufiq Ramadhan SY; Kiki Razroma Yantika (Smart International Management Journal, 2025)
Organizational climate plays an important role in shaping employee work behavior, especially in multicultural work environments. This study aims to analyze the effect of organizational climate on Organizational Citizenship Behavior (OCB) in a workplace with a high level of cultural diversity. Using a quantitative approach, data were collected through questionnaires from 60 respondents and analyzed using multiple linear regression. The results showed that organizational climate has a positive and significant influence on OCB, which means that the better employees' perception of organizational climate, the higher their tendency to show voluntary behavior that supports the organization. In contrast, the multicultural work environment does not have a significant influence on OCB, which indicates that cultural diversity needs to be managed with the right strategy so that it does not become an obstacle in building cooperation and solidarity between employees. The findings confirm the importance of organizations in creating a conducive work environment with open communication, strong managerial support, and inclusive policies to encourage positive employee behavior. This study provides insights for management practitioners in developing effective strategies to increase productivity and work harmony in a multicultural environment.